FIELD TRIP TEACHING METHOD: INTRODUCING EDUCATIONAL TOURISM (EDUTOURISM) FOR LEARNING ENGLISH - Nur Fitria, Tira (Journal of Language, Education, Literature, and Culture, 2024)
This research describes educational tourism (edu-tourism) for learning English. This research is library research. The analysis shows that Edu-tourism is a method that combines tourism and learning activities, often held by primary schools, even higher levels. Educational tourism is an attractive choice for all groups, including elementary, middle, and high school students. Educational tourism is a form of tourism that offers education to students as tourists or visitors through activities and fun methods. It allows them to understand and remember the learning process. This method helps to deepen understanding and remember the learning process, as it is often driven by boredom with rigid and formal learning methods. Visiting places where many people live abroad allow for interactive and entertaining educations. One popular educational tourism is English Village, a famous place in Indonesia with numerous English language course institutions. The village not only provides institution courses but also has fluent English-speaker residents. With a variety of interesting activities and a unique educational concept, English Village is an attractive tourist destination for students even tourists who want to learn English in a fun and effective way. The role of English villages as educational tourism in increasing the interest of immigrants is as a learning center that facilitates many English language course institutions and creates a learning environment that is different from formal education. The management of the course institution plays a role in creating a language environment to attract newcomers to learn English by involving a teacher who plays a direct role when interacting with students in the classroom. English Village not only showcases natural beauty but also serves as a place for learning foreign languages (English) for visiting tourists. It offers tourism activities that emphasize educational elements and involve tourists in direct contact with the local community. Overall, educational tourism provides a unique and engaging way for tourists to learn and enjoy the beauty of an area while also learning English.